1997
DOI: 10.1007/s004140050095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the immunohistology of mucosa-associated lymphoid tissue in the larynx and lungs in cases of sudden infant death and controls

Abstract: The respiratory tract of children in the first two years of life, unlike that of adults, contains bronchus-associated lymphoid tissue (BALT) and larynx-associated lymphoid tissue (LALT) with no differences in frequency between SID and control children. Using immunohistochemical methods we examined the distribution of B, T, CD4+ and CD8+ lymphocytes, HLA-D+ cells, CD68+ macrophages and proliferating cells, comparing bronchus-associated and larynx-associated lymphoid tissue of sudden infant death cases and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…1). A few proliferating cells positive for Ki67 were seen in the follicles and many cells positive for HLA-DR were evenly distributed over the follicle [15]. This basic structure distribution of lymphoid and nonlymphoid cells was also seen in BALT in pathological conditions, e.g.…”
Section: Microscopic Structure Of Baltmentioning
confidence: 55%
See 2 more Smart Citations
“…1). A few proliferating cells positive for Ki67 were seen in the follicles and many cells positive for HLA-DR were evenly distributed over the follicle [15]. This basic structure distribution of lymphoid and nonlymphoid cells was also seen in BALT in pathological conditions, e.g.…”
Section: Microscopic Structure Of Baltmentioning
confidence: 55%
“…There were no significant differences in the frequencies (36 versus 44%) or in the probability of finding BALT in different age groups. The immunohistology of the lymphocyte subset distribution was also comparable in the lungs of SIDS and trauma children [15]. Thus, BALT is not pathognomonic for SIDS.…”
Section: Balt In Sudden Infant Death Syndromementioning
confidence: 82%
See 1 more Smart Citation
“…In studies of SIDS, no differences have been found in the mucosal immunology of the respiratory tract. 35 It is therefore unlikely that the data are biased for SIDS.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in man [1][2][3] and animals [4,5] show that the larynx does contain immunological tissue. A minor part of this has been reported to be present in the form of epithelial follicles (larynx-associated lymphoid tissue: LALT [1]) in an age-and disease-dependent manner [1,6]. However, as with studies of gut [7] and trachea [8], the majority of immunologically active cells appear to be present in a more diffuse, although still organized manner [3,4].…”
Section: Introductionmentioning
confidence: 99%